2017
DOI: 10.1111/aor.12975
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal Membrane Oxygenation Can Save Lives in Children With Heart or Lung Failure After Liver Transplantation

Abstract: The risk of cardiac or lung failure after liver transplantation (LT) is significant. In rare cases, the usual intensive care techniques fail to maintain organ oxygenation with a risk of multiorgan dysfunction. Although extracorporeal membrane oxygenation (ECMO) is a difficult and risky procedure, it can be proposed as life-saving. Four children with either acute pulmonary (three) or cardiac (one) failure after LT, and the criteria that decided the use of ECMO (level of ventilation and results, dosage of inotro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…7,35 Additionally, many patients have an indication for LT associated with a condition predisposing them to either respiratory or cardiovascular failure as is seen with HPS, portopulmonary hypertension, pulmonary artery stenosis in Alagille syndrome, or cardiomyopathy of metabolic disease. 4,5,21,35,36 Many of these conditions can be acutely exacerbated by the hemodynamic changes associated with LT and result in mortality without the temporary respiratory and cardiovascular support provided by ECMO. Institution of ECMO after failure of traditional resuscitation measures has a survival of 28.6%-44.4% in adult LT patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,35 Additionally, many patients have an indication for LT associated with a condition predisposing them to either respiratory or cardiovascular failure as is seen with HPS, portopulmonary hypertension, pulmonary artery stenosis in Alagille syndrome, or cardiomyopathy of metabolic disease. 4,5,21,35,36 Many of these conditions can be acutely exacerbated by the hemodynamic changes associated with LT and result in mortality without the temporary respiratory and cardiovascular support provided by ECMO. Institution of ECMO after failure of traditional resuscitation measures has a survival of 28.6%-44.4% in adult LT patients.…”
Section: Discussionmentioning
confidence: 99%
“…From 24 articles initially identified as potentially eligible, 16 studies were retrieved for data extraction after fulltext review (Figure 2). The studies included in the present systematic review were published between 2000 and 2020 and were conducted in the United States (n = 7), 8,9,[18][19][20][21][22] Asia (n = 5), 7,12,[23][24][25] Europe (n = 3), [4][5][6] and Canada (n = 1). 26 A total of 22 children that received ECMO on the day of transplant or later were included in the systematic review (Table 4).…”
Section: Systematic Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Indications for ECMO include reversible circulatory and/or respiratory failure with inadequate oxygen delivery. There remains limited data on ECMO therapy for sepsis following LT. 1,2 Lee et al reported on ECMO rescue for refractory sepsis post-LT in a series of 8 adults and found 25% survival. 1 Of note, survivors exhibited prompt reduction in lactic acidosis after initiation of ECMO, similar to our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Jean et al of the Hôpital Armand‐Trousseau, Paris, France investigated the use of ECMO in four children with either pulmonary of cardiac failure after liver transplantation. Two achieved a full recovery with 3‐ and 6‐years follow up while two died of systemic inflammatory response syndrome due to ECMO.…”
Section: Cardiopulmonary Support and Membrane Oxygenationmentioning
confidence: 99%